Pengaruh Profitabilitas, Pertumbuhan Perusahaan, Leverage, Likuiditas, serta Struktur Modal terhadap Nilai Perusahaan - Ni Kadek Riesna Yusmita; I Nyoman Kusuma Adnyana Mahaputra; Putu Ayu Meidha Suwandewi (Jurnal Inovasi Akuntansi (JIA), 2023)
This research was conducted to analyze the effect of Profitability, Company Growth, Leverage, Liquidity, and Capital Structure on the Value of manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The research population is a manufacturing company listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample of this research were 84 companies which were determined using a purposive sampling method. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that the Company's Growth has a positive effect on firm value. While the variables of Profitability, Leverage, Liquidity, and Capital Structure have no effect on firm value.